Wellbeing in dementia : an occupational approach for therapists and carers - Perrin, Tessa; May, Hazel; Anderson, Elizabeth D. Phil.; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone/Elsevier, 2008)
The authors, specialists in the UK, draw on developmental theory to propose a model of practice specifically for dementia care. The number of people who suffer from dementia is increasing and in consequence the problems it presents are affecting a growing number of therapists and carers. Many of these problems are peculiar to dementia and the models of care used with other client groups have proved inadequate when dealing with the provision of quality of care to people who have dementia. This revised edition contains a new opening chapter which brings our understanding of dementia up-to-date. The book looks at the relationship between occupation, wellbeing and dementia and examines the critical role of the carer in developing therapeutic interventions. Proposes a realistic model of practice for dementia care which centres on the unique occupational potential of the person with dementia. Offers positive strategies to improve wellbeing. Current information on assessment tools. Written by therapists with extensive experience in working with this client group.
Understanding dementia -- Occupational therapy revisited -- The altered world of dementia -- The significance of the carer -- The playful practitioner -- Principles of good practice in dementia care -- Non-verbal communication: the currency of wellbeing -- A model for dementia care -- Assessing capacity for doing and promoting engagement -- The dementia therapist : a good enough mother?
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Senile dementia -- Treatment; Occupational therapy for older people; MEDICAL -- Gynecology & Obstetrics; Occupational therapy for older people; Senile dementia -- Treatment; Dementia -- rehabilitation; Occupational Therapy -- methods; Patient Care; Beschäftigungstherapie; Demenz; Managed Care; Wohlbefinden; Electronic books